2012
DOI: 10.1350/ijep.2012.16.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Embracing the Overriding Objective: Difficulties and Dilemmas in the New Criminal Climate

Abstract: There has been little discussion to date of the impact of the new criminal case management system enshrined in the Criminal Procedure Rules for England and Wales upon the judges and practising lawyers who are expected to operate it. Detailed interviews were conducted with a number of these criminal law professionals in order to explore what, if any, problems they were experiencing in this context. It transpires that a number of practical problems confront them, and that defence lawyers may have difficulty reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Darbyshire (2014, see also Darbysihre, 2011Garland & McEwan, 2012: 248-250) has found in the majority of Crown Courts that she observed, and consist of reprimands:…”
Section: Judge#01mentioning
confidence: 99%
See 3 more Smart Citations
“…Darbyshire (2014, see also Darbysihre, 2011Garland & McEwan, 2012: 248-250) has found in the majority of Crown Courts that she observed, and consist of reprimands:…”
Section: Judge#01mentioning
confidence: 99%
“…Commentators have indicated that such shifts are difficult to achieve, especially with respect to the parties of the process (Quirk, 2006). Prosecutors and defence barristers alike are still immersed in the longstanding adversarial tradition, resources are scarce on both sides with regard to the onerous disclosure process, and there are no effective sanctions for reprimanding participants who impair the procedural efficiency of the trial (McEwan, 2011;Redmayne, 2003 (Hodgson, 2010;McEwan, 2011;Garland & McEwan, 2012). At its root is the notion of party rather than judicial control over the case, and the process relies on the "lawyer-partisans responsibility for gathering, selecting, presenting, and probing the evidence" (Langbein, 2003: 2).…”
Section: Complex Fraud Trials Managerialism and Procedural Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…But the massive amount of information and the complexity of possible interrelations between elements of unused materials in complex investigations raise questions about the capacity of solicitors to process the material effectively. There are material disincentives for defence lawyers: under the graduated fixed fee system now used to fund legal aid, solicitors get a sum based on the number of pages disclosed, not the time taken to read them (Garland and McEwan, 2012: 245; Nurse, 2013: 77). Defence solicitors do not have access to the HOLMES computer technology used by the police to organise complex investigations and only the more specialist use Case Map (the equivalent for defence lawyers).…”
Section: Adversarial Truth-finding In England and Walesmentioning
confidence: 99%